Does the addition of AMACR to CK20 help to diagnose challenging cases of urothelial carcinoma in situ? - Erin L. J. Alston; Debra L. Zynger (BMC, 2019)
Abstract Background Urothelial carcinoma in situ (CIS) in the bladder can be difficult to diagnose due to factors including procedural artifact, minimal tissue sampled, therapy-related changes, and various CIS growth patterns. Prior data has demonstrated an increase in alpha-methylacyl-CoA-racemase (AMACR) in urothelial CIS, but there is no information on its utility for diagnosing difficult cases. The aim of this investigation was to assess the expression of AMACR that was ordered on equivocal bladder cases during clinical practice. Methods Transurethral resections of the bladder in which AMACR and CK20 were performed during diagnostic workup were identified and cases with a final diagnosis of CIS (n = 22) or non-neoplastic urothelium (n = 30) were selected. Additionally, cases in which a diagnosis of CIS was rendered without IHC (n = 20) were selected and tested for AMACR expression. Results Sensitivity of AMACR for CIS diagnosed with IHC during clinical practice was 73% and specificity was 97%, while CK20 was 95% sensitive and 80% specific. Sensitivity of AMACR in CIS diagnosed without IHC was 100%. In all groups, AMACR had inconsistent intensity, compared to CK20 which had consistent, strong intensity. Conclusions AMACR was usually positive in urothelial CIS and negative in non-neoplastic urothelium. However, it is important to note that AMACR was less sensitive in difficult cases, while CK20 was more sensitive with more consistent, strong staining compared to AMACR.